Fabricating Patient-customizable Tubular Scaffolds From Biodegradable Polymer - Chian, Kerm Sin (2016)
A polymeric scaffold for guiding the cell growth is designed and fabricated, which could be useful for the tissue engineering (TE) of tubular organs including esophagi, blood vessels, and tracheas. This tubular scaffold was fabricated via a melt-drawing of highly elastic poly(Llactide- co-ε-caprolactone) (PLC) fibers layer by layer on a cylindrical mandrel. Diameter of the scaffold is customizable by 3D printing of the mandrel. The morphology, crystallinity, and mechanical properties of the PLC fibers were investigated. The fibers were highly aligned and have a uniform diameter. Fiber diameters and tensile properties were tuneable with varying melt-drawing speeds. These tailorable topographical and tensile properties show that the scaffold fabrication technique is micro- and macro-scale customizable for different tubular tissues. The potential of these scaffolds in TE was further exhibited by the finding that smooth muscle and fibroblast cells seeded onto the scaffolds in vitro showed appropriate cell proliferation and distribution.